2016
DOI: 10.1038/cmi.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

CD205-TLR9-IL-12 axis contributes to CpG-induced oversensitive liver injury in HBsAg transgenic mice by promoting the interaction of NKT cells with Kupffer cells

Abstract: Gut-derived bacterial products contribute to liver inflammation and injury during chronic hepatitis B virus infection; however, the underlying mechanisms remain obscure. In this study, hepatitis B surface antigen transgenic (HBs-Tg) mice and their wild-type (WT) control C57BL/6 mice were injected with CpG-oligodeoxynucleotides (ODNs) to mimic the translocation of gut microbial products into the systemic circulation. We found that, compared with the WT mice, the HBs-Tg mice were oversensitive to CpG-ODN-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…Our recent study showed that a population of CD205 + macrophages accumulated in the liver of hepatitis B surface antigen transgenic (HBs-Tg) mice. These CD205 + macrophages contributed to HBs-Tg mice having greater amounts of IL-12 and severer liver injury than B6 mice20. In the present study, we characterised CD205 + macrophages in the liver of HBs-Tg mice and found that CD205 + macrophages had a more pro-inflammatory phenotype and function than CD205 − macrophages.…”
supporting
confidence: 47%
See 1 more Smart Citation
“…Our recent study showed that a population of CD205 + macrophages accumulated in the liver of hepatitis B surface antigen transgenic (HBs-Tg) mice. These CD205 + macrophages contributed to HBs-Tg mice having greater amounts of IL-12 and severer liver injury than B6 mice20. In the present study, we characterised CD205 + macrophages in the liver of HBs-Tg mice and found that CD205 + macrophages had a more pro-inflammatory phenotype and function than CD205 − macrophages.…”
supporting
confidence: 47%
“…We previously reported that the levels of macrophage-derived cytokines IL-12 and TNF-α were higher in the serum of HBs-Tg mice than those in B6 mice after treatment with CpG-ODNs20, which suggests that hepatic macrophages in HBs-Tg mice are more sensitive to bacterial DNA. To confirm this in the present study, we isolated hepatic macrophages from HBs-Tg and B6 mice and assessed the function of the cytokines produced after stimulation with CpG-ODNs or commensal Escherichia coli (E. coli ) DNA.…”
Section: Resultsmentioning
confidence: 92%
“…For example, investigators have demonstrated that during APAP‐induced liver injury, necrotic hepatocytes release mtDNA, which acts as an agonist for Toll‐like receptor 9 (TLR9) to induce neutrophil infiltration and liver inflammation that may further exacerbate hepatocellular damage . In addition, the pathological role of TLR9 activation in inducing neutrophil infiltration and liver injury has also been reported in other liver injury models, including liver ischemia/reperfusion, chronic‐plus‐binge ethanol feeding, nonalcoholic fatty liver disease, and hepatitis B surface antigen transgenic mice . However, how the inflammation is terminated in APAP‐induced hepatotoxicity remains largely unknown.…”
mentioning
confidence: 99%
“…(7)(8)(9) In addition, the pathological role of TLR9 activation in inducing neutrophil infiltration and liver injury has also been reported in other liver injury models, including liver ischemia/reperfusion, (10)(11)(12) chronic-plus-binge ethanol feeding, (13) nonalcoholic fatty liver disease, (14) and hepatitis B surface antigen transgenic mice. (15) However, how the inflammation is terminated in APAP-induced hepatotoxicity remains largely unknown.…”
mentioning
confidence: 99%
“…These data CD205-expressing KCs respond to CpG-ODNs and subsequently release IL-12 to promote NKT cell activation. Activated NKT cells induce liver damage through the Fas-signaling pathway in HBs-Tg mice [98].…”
Section: Liver Infection By Virusesmentioning
confidence: 99%